Construction of ecological security pattern of Jiangnan water town considering water-related ecosystem services: a case study of Yuecheng District, Shaoxing - Meizi Zhou; Yong He; Yonghua Li; Jialei Wang; Song Yao (Geocarto International)
The ecological security pattern (ESP) is considered an effective method to balance urban development and ecological protection. Integrating water-related ecosystem services (ESs) into the ESP construction process is essential for protecting urban water systems. In this study, Yuecheng District, a typical Jiangnan water town, was selected as the study area. We combined water-related ESs hotspots, landscape connectivity analysis and ecological resistance surfaces to identify areas that should be prioritized for restoration. The results indicated that (1) 25 ecological sources were identified, mainly distributed in the central canal water network area and the southern mountainous area; (2) we extracted 51 ecological corridors, with 44 of these being blue ecological corridors overlapping with rivers; (3) we developed a spatial optimization scheme known as “two belts, one circle and three zones” based on the ESP. This study offers valuable insights for sustainable planning and refined river and lake management in Jiangnan Water Town.